THE EFFECT OF POPULATION AND PMDN ON GRDP IN NORTH SUMATRA 2001-2020 PERIOD - Segoro, Ega Bayu; Evander Pardos, Evander; Nadeak, Feronika Daoni; Ginting, Hawariyah; Aulia, Shafa; Hidayat, Nasrullah; Hutasuhut, Saidun (Quantitative Economics Journal, 2023)
The Gross Regional Domestic Product (GDP) is the main indicator of the economic condition of a region at all times, either based on current prices or constant prices. Total population and domestic investment have an impact on increasing and decreasing GRDP of a region. An increase in population is likely to increase the GRDP of a region, as will an increase in domestic investment, especially in the form of employment which will increase domestic productivity.